Internet solutions for project managers - Maitra, Amit K. 1947- (Wiley, 1999)
"Empowered by a new generation of Internet technologies and Web applications, managers can now work together from virtually anywhere in the world and on any platform to manage and complete a project. In this book, Internet expert Amit Maitra describes how to successfully exploit the power and versatility of the Internet as a tool for managing projects and processes, and how you can too." "Maitra provides managers with clear, step-by-step guidelines for designing, developing, and implementing Interner approaches customized to an organization's unique project management needs - and supplies helpful ideas for assessing the performance and ROI of project management Internet applications."--Jacket.